Response of Microorganism Suspension and Various Kinds of Organic Fertilizers to the Development of Pathogen Fusarium sp. on Shallots - Ratna Arifiani Sukmaningrum; Sri Wiyatiningsih; Endang Triwahyu Prasetya; Retno Sulistiyowati (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2023)
Shallot (Allium ascalonicum L) is one of the horticultural plants that acts as a natural antioxidant. Shallot's productivity in Indonesia is relatively low. It is influenced by various factors, one of which is due to the attack of a soil-borne pathogen, namely Fusarium oxysporum. Symptoms of Fusarium oxysporum pathogen attack are yellow or pale green leaves and more elongated growth. Severe attack leads plant to death. Balanced fertilization and biopesticides application can prevent Fusarium wilt. This study aims to reduce and control Fusarium wilt disease. The research method used was the Split Plot Design method which consisted of two factors with the main plot, namely the application of suspension of microorganisms (S) which consists of two levels, namely fungicide application (S0) and Fobio application and the sub-plot, namely the application of various organic fertilizers (M) which consists of three levels, namely control (chemical fertilizer) (M0), chicken manure (M1), and Piensbio organic fertilizer (M2). Observation data for each treatment will be analyzed using analysis of variance (ANOVA) followed by the Duncan test (alpha 5%) if there were differences in each treatment. The results of this study, the main plot treatment, fungicide application (S0), showed an incubation period of 29 days and an average intensity of disease attacks of 4.2%. The treatment of subplots, a type of organic fertilizer (M), is unable to suppress the intensity of the attack and slow down the incubation period of the Fusarium sp on shallot crops. There was no interaction between the treatment of the main plots and the subplots on all the observation parameters.